Webinar "How to Communicate with Non-Verbal Children: Using Picture Exchange Communication System (PECS)" - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
The webinar "How to Communicate with Non-Verbal Children: Using Picture Exchange Communication System (PECS) was conducted on 27th August 2022, Saturday. The purpose of this webinar was to share the knowledge of effective communication between parents and their down syndrome and cerebral palsy children (who are mostly non-verbal). The invited speaker was Mr Muhammad Azwan Azri, a lecturer from the Occupational Therapy Department (Pediatric) at UiTM Pulau Pinang. The sharing session also demonstrated how to utilise PECS tool to communicate with the children. The audience of this webinar included parents from ORKIDS and MyCP organisations, as well as the public in general.